Public support for body-worn cameras: the need for inclusion of more comprehensive measures of public concerns - Kopp, Phillip M. (Criminal justice studies, 2021)
Research finds that the public generally supports the use of Body-Worn Cameras (BWC) by police. Much of the support for BWCs is attributed to the technology’s ability to promote police accountability and enhance perceptions of law enforcement transparency, while also providing support to uniformed personnel. However, we do not really know why the public supports BWC usage by police because research on the technology’s potential benefits and related deployment issues is still in its infancy. The few studies that have sought to unravel the predictors of public support for BWC have focused their attention on the benefits the public perceives will accompany the use of BWC to the virtual exclusion of the concerns they may have with the technology. Using survey data collected from 431 residents of a mid-size city in Southern California, this study expands our knowledge of the influences of public support for BWC by including a comprehensive measure of the public’s perceived concerns, including privacy, cost, technology limitations, and the possible manipulation of BWC footage. Findings revealed that public support was significantly influenced by respondents’ perceived benefits and their perceived concerns about BWC, while controlling for demographic characteristics.